Experimental study on early cracking sensitivity of lightweight aggregate concrete. (1st April 2017) - Wang, X.F.; Fang, C.; Kuang, W.Q.; Li, D.W.; Han, N.X.; Xing, F.
Highlights: Lightweight aggregate concrete (LWAC) has a lower cracking sensitivity than normal-weight concrete. Prewetted ceramsite and expansive agent can minimize early cracks. Partial replacement of aggregates by ceramsite reduces cracking sensitivity. A model is presented for the relationship between the moisture content of ceramsite and the restraining stress. Abstract: In this study, experimental investigations are reported on the effects of the moisture content of ceramsite, the replacement rate of aggregates, and the use of expansive agent on the early cracking sensitivity of lightweight aggregate concrete. Three kinds of commercially available lightweight aggregates (clay ceramsite, shale ceramsite, fly ash-clay ceramsite) were used in the experiment. The cracking sensitivity of concrete was investigated via splitting tensile test, plate cracking test and temperature-stress test. The results showed that the cracking sensitivity of concrete decreased with the increases in the moisture content and the replacement rate of aggregates. A model describing the relationship between the moisture content of ceramsite and the restraining stress was presented.